2007
DOI: 10.1016/j.cub.2007.08.047
|View full text |Cite
|
Sign up to set email alerts
|

An AMPK-FOXO Pathway Mediates Longevity Induced by a Novel Method of Dietary Restriction in C. elegans

Abstract: Our study shows that an energy-sensing AMPK-FOXO pathway mediates the lifespan extension induced by a novel method of dietary restriction in C. elegans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
722
6
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(785 citation statements)
references
References 56 publications
(98 reference statements)
36
722
6
5
Order By: Relevance
“…In the first instance, we diluted the amount of bacteria (provided as a nutritional source for the nematodes) to which the nematodes were exposed. This intervention was already shown to extend lifespan (Greer et al, 2007). We also subjected worms to a complete bacterial deprivation as of their first day of adulthood.…”
Section: Resultsmentioning
confidence: 89%
“…In the first instance, we diluted the amount of bacteria (provided as a nutritional source for the nematodes) to which the nematodes were exposed. This intervention was already shown to extend lifespan (Greer et al, 2007). We also subjected worms to a complete bacterial deprivation as of their first day of adulthood.…”
Section: Resultsmentioning
confidence: 89%
“…Chronic food limitation increases lifespan by downregulating TOR activity, which increases autophagy and diminishes translation, probably through PHA‐4/FOXA transcription factor and S6 kinase, respectively, in a DAF‐16/FoxO‐independent manner (Kaeberlein et al ., 2005; Hansen et al ., 2007; Pan et al ., 2007; Sheaffer et al ., 2008). AMPK (AMP kinase), an energy sensor for cellular AMP/ATP ratio that enables catabolic reactions for energy gain, has been shown to respond to dietary restriction by increasing stress resistance and extending longevity in C. elegans in a DAF‐16/FOXO‐dependent manner (Apfeld et al ., 2004; Greer et al ., 2007a). AMPK directly phosphorylates and activates DAF‐16/FoxO (Greer et al ., 2007a).…”
Section: Animal Modelsmentioning
confidence: 99%
“…AMPK (AMP kinase), an energy sensor for cellular AMP/ATP ratio that enables catabolic reactions for energy gain, has been shown to respond to dietary restriction by increasing stress resistance and extending longevity in C. elegans in a DAF‐16/FOXO‐dependent manner (Apfeld et al ., 2004; Greer et al ., 2007a). AMPK directly phosphorylates and activates DAF‐16/FoxO (Greer et al ., 2007a). Dietary restriction with every‐other‐day feeding is likely to promote C. elegans longevity via downregulation of the IIS pathway (Honjoh et al ., 2009).…”
Section: Animal Modelsmentioning
confidence: 99%
“…For example, in anoxic myocardial cells, upregulation of AMPK can decrease the phosphorylation level of FOXO1 and FOXO3, and exclusion of them from the nucleus, leading to sequential activation of target genes, such as catalase (62). It has been demonstrated that AMPK phosphorylates the FOXO homologue, DAF-16, at multiple sites and activates DAF-16-dependent transcription (63). Notably, DAF-16 can induce the expression of genes encoded by AMPK, which slows aging in Caenorhabiditis elegans.…”
Section: Adenosine Monophosphate-activated Protein Kinase (Ampk)mentioning
confidence: 99%